Winding optimization of composite frame by dry fiber rovings. (23rd September 2022) - Mlýnek, Jaroslav; Petrů, Michal; Ryvolová, Martina; Rahimian Koloor, Seyed Saeid
Light-weight fibers reinforced polymer (FRP) composite frames are essential parts of vehicles body in the aerospace and automotive industries. Composite frames are often designed in complex curved 3D geometry through the dry winding process. The winding process of homogeneously wound-up layers of fibers without overlapping and gaps is the main challenge in the fabrication of frames with consistent thickness and acceptable quality. In this study, an industrial robot and winding head are set with a novel optimum process to wind the dry fiber with the specified angles on the frame, to fabricate it with minimum overlapping and local commulation of fibers, yet without gaps. Mathematical models and algorithms are developed to determine the optimal number of simultaneously wounds rovings of fibers in a given layer. In addition, this study addresses the optimum dry winding of curved parts of frames that form a torus geometry. It is shown that the combination of layers of rovings wound successively on the frame at angles of 45°, 90° (i.e. the rovings are laid along with the frame), and −45°, is the most used variant of winding that provides the composite frame with higher strength. Results indicated that an optimal selection of the number and width of the rovings minimizes the overlap of the wound rovings, which saves up to 20% of the utilized fibers. The derived theory is verified on practical tests and experiments, which confirms the development of new suitable procedures to improve the fabrication of FRP composite frames.